Dampak Ekspor Terhadap Perkembangan Perekonomian Indonesia - Suci Frisnoiry; Stevania Sri Debbye Br Simbolon; Jesiska Anjelin Siagian; Imel Simanungkalit (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The economy is very important for the survival and development of a country. This research shows the impact of exports on Indonesia's economic growth. In this research, circumstances, conditions or other factors, are investigated and the results are recorded in a research report. Stability testing is required before starting analysis. Indonesia's exports fell 4.89 percent to $14.18 billion in December 2018, meaning that the economy will shrink between 2018 and 2021. It is hoped that this research will help the government and authorities to take appropriate steps to improve the Indonesian economy.